2017
DOI: 10.1186/s13287-017-0608-0
|View full text |Cite
|
Sign up to set email alerts
|

Influences of age-related changes in mesenchymal stem cells on macrophages during in-vitro culture

Abstract: Background: Mesenchymal stem cells (MSCs) have been widely used in cytotherapy and tissue engineering due to their immunosuppressive ability and regenerative potential. Recently, the immunomodulatory influence of MSCs has been gaining increasing attention because their functional roles in modulating immune responses likely have high clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 70 publications
0
37
1
Order By: Relevance
“…Immune reactions following implantation in vivo is vital to the prognosis of biomaterials in BTE and a new in-vitro assessment approach with inclusion of macrophages has gradually become the main evaluating criterion for the osteogenesis of new fabricated materials [ 2 , 8 ]. Along with advances in the understanding of the divergent effects of distinct subtypes of macrophages (M1 and M2) in tissue regeneration, more and more attention has focused on the strategies for modulating the immune microenvironment around the implants [ 32 ]. The immunomodulatory properties of MSCs on macrophages provides a new means for promoting tissue regeneration and it has been suggested that it be incorporated in design of tissue engineering materials [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune reactions following implantation in vivo is vital to the prognosis of biomaterials in BTE and a new in-vitro assessment approach with inclusion of macrophages has gradually become the main evaluating criterion for the osteogenesis of new fabricated materials [ 2 , 8 ]. Along with advances in the understanding of the divergent effects of distinct subtypes of macrophages (M1 and M2) in tissue regeneration, more and more attention has focused on the strategies for modulating the immune microenvironment around the implants [ 32 ]. The immunomodulatory properties of MSCs on macrophages provides a new means for promoting tissue regeneration and it has been suggested that it be incorporated in design of tissue engineering materials [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the present study, the osteogenesis of rBMSCs in the 12.5 μg/mL Lap group was significantly higher than in the other groups. This may be attributed to the following: first, compared with the other groups, flow cytometry implicated less M1 polarization in the 12.5 μg/mL Lap group with a higher expression of anti-inflammatory factors such Arg-1 and IL-10 which are beneficial for osteogenesis [ 32 , 40 ]. Second, the production of proinflammatory factors such as IL-1β, TGF-β, and IL-6 is relatively low in the 12.5 μg/mL Lap group.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that stimulating factors were completely removed before the supernatants of polarized Mφs were collected for CM production . In addition, the application of CM in investigations can prevent changes in Mφ polarization when directly co‐cultured with BMMSCs, as there is evidence that MSCs exert significant effects on macrophages during in vitro culture . Given that cell sheets generated by stem cell cultures are widely used as cellular materials in regenerative design, we also investigated the influence of various Mφs on matrix production and stem cell sheet formation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the immunosuppressive potential of MSCs derived from bone marrow, adipose, and other sources is negatively in uenced by aging (14,15). In our previous studies, we showed that PDLSCs not only have the ability to reconstruct the periodontal tissue and bone defects (16,17), but also have low immunogenicity and strong immune regulation ability (18).…”
Section: Introductionmentioning
confidence: 91%